The Aplications Biological Control of the Pest Population ( Plutella xylostella Linn. And C. pavonana Zell.) and Their Natural Enemies in Cabbage Plants in the Village Kalibaru Kulon, District Banyuwangi - Helmi Helmi; Didik Sulistyanto; Purwatiningsih Purwatiningsih (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2015)
The aim of the research was to determine the effectiveness of biological control agens to the population of pests and their natural enemies in cabbage crops in agricultural land Kalibaru kulon Kab. Banyuwangi. The research was conducted by Randomized Complete Block Design with with five replications. The treatments were Control as P0, Heterorhabditis sp. as P1, Bacillus thuringiensis as P2, Profenofos as P3, Beauveria bassiana as P4, Red bacteria as P5. Data were obtained from observations of pest population and their natural enemies, as well as the percentage decrease in the population of pests and their natural enemies. Data were analyzed using ANOVA and LSD were tested further by 5%. The results showed that Heterorhabditis sp. was the most effective agents to control populations of Plutella xylostela Linn. and Crocidolomia pavonana Zell., this is also indicated by a decrease in pest population of Plutella xylostela by 54.66% and amounted to 47.9% Crocidolomia pavonana. Aplication biological agens was not affect the population of natural enemies Coccinela repanda, and Verania sp. Keywords : Cabbage, Biological Control, Pests, Natural enemies